Efficient and Sustainable in situ Photo‐Fenton Reaction to Remove Phenolic Pollutants by NH2‐MIL‐101(Fe)/Ti3C2Tx Schottky‐Heterojunctions - Hu, Cong‐Yi; Jiang, Zhong‐Wei; Yang, Chang‐Ping; Wang, Xiao‐Yan; Wang, Xue; Zhen, Shu‐Jun; Wang, Dong‐Mei; Zhan, Lei; Huang, Cheng‐Zhi; Li, Yuan‐Fang (Chemistry : a European journal, 2022)
Metal‐organic frameworks (MOFs) with abundant active sites, a class of materials composed of metal nodes and organic ligands, is widely used for photocatalytic degradation of pollutants. However, the rapid recombination of photoinduced carriers of MOFs limits its photocatalytic degradation performance. Herein, Ti3C2Tx nanosheets‐based NH2‐MIL‐101(Fe) hybrids with Schottky‐heterojunctions were fabricated by in situ hydrothermal assembly for improved photocatalytic activity. The photodegradation efficiencies of the NH2‐MIL‐101(Fe)/Ti3C2Tx (N‐M/T) hybrids for phenol and chlorophenol were 96.36 % and 99.83 % within 60 minutes, respectively. The N‐M/T Schottky‐heterojunction duly transferred electrons to the Ti3C2Tx nanosheets surface via built‐in electric fields, effectively suppressing the recombination of photogenerated carriers, thereby improving the photocatalytic performance of NH2‐MIL‐101(Fe). Moreover, the Fe‐mixed‐valence in the N‐M/T led to improvement in the efficiency of the in situ generated photo‐Fenton reactions, further enhancing the photocatalytic activity with more generated reactive oxygen species (ROS). The study proposes a highly effective removal of phenolic pollutants in wastewater. The built‐in electric field formed in NH2‐MIL‐101(Fe)/Ti3C2Tx Schottky‐heterojunction hybrids coupled with in situ photo‐Fenton‐like reactions to remove phenolic pollution under the visible light irradiation is described.